KEUPAYAAN KOMUNITI KEUSAHAWANAN DALAM KALANGAN SUKU KAUM ORANG KUALA DI RENGIT, JOHOR - Ahmad Hariri, Tun Ili Ayuni; Roddin, Rohayu; Mohamad, Mimi Mohaffyza; Asri, Mohd Anis; Ghazalan, Mohd Shahzuan (Online Journal for TVET Practitioners, 2018)
Orang Asli isknown to have natural skills because they are able to survive by relying on the nature-based nature of the eco-economy where they live. The economic results they get are from forest produce, as well as marine produce. They are skilled in making handicrafts, making plaiting, processing, food hunting and so on. In the beginning they were merely changing items but the longer they were clever in trading activities among local communities and outside communities. This can be seen through the communities that managed to open their own businesses such as Orang Asli in Rengit. They have successfully made this entrepreneurial activity a major quest. These business activities originally from individual engagement have become a business in one community as the number of businesses in this community who sell the same products are growing. The purpose of this paper is to see how the capabilities of the Kuala Orang Orang Asli community in entrepreneurship from the aspects of economics, psychology and sociology.